Dr. Seuss' how the Grinch stole Christmas [videorecording (DVD)] - Howard, Ron, 1954-; Carrey, Jim, 1962-; Tambor, Jeffrey, 1944-; Baranski, Christine; Hopkins, Anthony, 1937-; Seuss, Dr (Universal, 2001)
Why is the Grinch such a grouch? No one seems to know, until little Cindy Lou Who takes matters into her own hands and turns both Whoville and the Grinch's world upside down, inside out, and funny side up in her search for the true meaning of Christmas.